A Study Review of Completion Multi Job on Job Shop Scheduling Technique To Minimize Make Span - Hery Irwan (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2020)
In this paper, the development of flexibility job shop scheduling problem was many discussed before globally. The concept job shop scheduling had discussion like minimize total make span, throughput approaching, lot streaming, no-wait job shop, and many more. Also, into job shop scheduling always consider deadline or due date for job load into machine available with target at the end how to optimize machine capacity and minimum make span.